AI Assisted Health Monitoring and Digital Inclusion for Emotional Security Among Older Adults (Health, Empathy, and AI Learning (HEAL), 2026)
The growing population of older adults has increased the need for accessible and sustainable healthcare support, particularly through digital technologies that enable continuous health monitoring. Recent developments in artificial intelligence have expanded the use of AI assisted health monitoring systems, including wearable devices and remote health applications, to support daily healthcare management among older adults. Beyond clinical functions, these technologies may also contribute to emotional well-being by strengthening feelings of safety and supporting digital inclusion. However, limited qualitative research has examined how older adults experience AI assisted health monitoring in relation to emotional security and access to digital healthcare. This study investigates the role of AI assisted health monitoring in supporting digital inclusion and emotional security among older adults. A qualitative descriptive approach was employed using semi structured interviews with older adult participants who had experience using digital health monitoring technologies. The collected data were analyzed through thematic analysis to identify recurring experiences and perspectives. The findings indicate that AI assisted health monitoring contributes to a stronger sense of emotional security by helping older adults monitor health conditions more consistently and reducing uncertainty regarding daily health management. Family assistance also plays an important role in supporting digital inclusion, while technology related barriers remain a challenge for some participants. These findings highlight the importance of designing human centered AI healthcare systems that are accessible and emotionally supportive for aging populations. The study contributes to discussions on healthy aging, digital inclusion, and empathetic healthcare innovation within AI based healthcare environments.